A metáfora em propaganda multimodal: criatividade e recontextualização - um enfoque da Linguística Sistêmico-Funcional - Katayama, Fernando Akimitsu (2020)
Good advertising as an element of marketing communication is essential to reach mass-market consumers and, therefore, more and more advertisers are planning a more harmonious combination between their messages and the media in which they are broadcast, with the aim of persuading the reader. Metaphorical creativity, in this sense, becomes a fundamental resource for creative professionals and researchers see it as a phenomenon that involves traits of cognition, semantics and discoursepragmatic studies, with strong persuasive appeal, in which the importance of the context is affirmed as a determining condition for their understanding. This approach combines with the notion of recontextualization, taking into account that most of the metaphors in everyday language are not new ones, but, instead, make use of familiar scenarios to give rise to new meanings. In contemporary society, meaning requires not only the analysis of language in the text, but also of the other semiotic resources that operate in the construction of semiotic artifacts, what is known as multimodal text. The objective of this master’s thesis is to examine the creative recontextualization of the RACE, WAR and JOURNEY metaphors used for persuasive purposes in multimodal advertisements published by the Folha de S.Paulo newspaper. This research answers the following questions: (a) How is persuasive advertising done in the RACE, WAR and JOURNEY source domains? (b) What is the role played by the highlighting and hiding process in the persuasive ads? and (c) How is the interaction between verbal and visual modes made in the constitution of persuasive strategies through metaphorical creativity? Verbal analysis is supported by Systemic-Functional Linguistics, a linguistic theory that relates the microstructure of the text's lexicogramatical choices to the macrostructure of the underlying meanings of the discourse. Visual analysis is based on the grammar of visual design approach, also based on systemic-functional theory. The research shows the double nature of the metaphor, which is not only conventional, but also innovative, in its support for modern advertising in verb-visual multimodality